Cascade of care for people living with HIV infection in Southern Brazil: results from a public health network - Ingridt Hildegard Vogler; Daniela Frizon Alfieri; Heloisa Damazio Bruna Gianjacomo; Elaine Regina Delicato de Almeida; Edna Maria Vissoci Reiche (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: The cascade of care for people living with HIV infection (PLHIV) describes steps in diagnosis, linkage and retention in care, as well as the provision and success of combination antiretroviral therapy (cART). The aim of this study was to evaluate the rates regarding the retention in care, on cART, and suppressed viral load for PLHIV attended at a Brazilian public health network. Data on PLHIV from 116 cities of Paraná, Southern Brazil, attended from 2012 to 2015, were retrospectively collected through the Laboratory Tests Control System (SISCEL). The number of PLHIV related to care increased about 22.5% from 2012 to 2015 (4,106 to 5,030 individuals). The proportion of PLHIV retained in care showed a trend toward stabilization around 81.7-86.9%. Every year, the use of cART increased up to 90.3% for PLHIV retained in care. Viral load suppression was achieved by 72.8% of patients on cART and 57.1% by those linked to care. Retention in care and HIV viral suppression were more likely to occur in older PLHIV than younger ones; similarly, patients living in medium-sized cities were more susceptible to these factors than in large- or small-sized cities. In conclusion, the study showed a high level of retention in care and HIV suppression on cART, as well as emphasized that current efforts for treating already-infected PLHIV remain a challenge for our health public institutions and may contribute to highlight steps for improvement of the HIV cascade of care in our population.